Alterations in miRNA expression patterns in whole blood of OSCC patients - Ries, Jutta; Vairaktaris, Eleftherios; Kintopp, Rita; Baran, Christoph; Neukam, Friedrich Wilhelm; Nkenke, Emeka (In Vivo, 2014)
Aberrant microRNA (miRNA) expression in blood of cancer patients is a common finding. The present study aimed at evaluating the differences in miRNA expression in whole blood samples of oral squamous cell carcinoma (OSCC) patients compared to healthy controls.Microarray based miRNA profiling was performed on whole blood samples of 20 OSCC patients and 20 healthy volunteers and the differences in expression patterns between the two groups were evaluated. The results were validated by Reverse Transcription quantitative-Polymerase Chain Reaction (RT-qPCR) in 50 OSCC patients and 35 volunteers.21 miRNAs were identified to be significantly differentially expressed in whole blood of OSCC patients compared to healthy controls. The impact of miR-186 (p=0.002), miR-494 (p=0.001) and miR-3651 (p=0.0001) could be validated by RT-qPCR.The aberrant expressions of miR-186, miR-494 and miR-3651 in whole blood of OSCC patients may serve as the basis for establishing minimally-invasive screening methods for OSCC based on miRNAs as biomarkers.
EVALuna2:24185

miR-186, miR-3651 and miR-494: Potential biomarkers for oral squamous cell carcinoma extracted from whole blood - Ries, Jutta; Vairaktaris, Eleftherios; Agaimy, Abbas; Kintopp, Rita; Baran, Christoph; Neukam, Friedrich Wilhelm; Nkenke, Emeka (Oncology Reports, 2014)
microRNAs (miRNAs) are aberrantly expressed in the whole blood of patients suffering from different types of cancer. Collection of whole blood samples is a minimally invasive procedure. To date, little is known concerning the altered miRNA expression in patients suffering from oral squamous cell carcinoma (OSCC). The present study aimed to evaluate the difference in miRNA expression in whole blood samples in OSCC patients as compared to healthy volunteers who served as controls. In 20 blood samples from patients and healthy volunteers, the expression patterns of 1,205 human miRNAs were examined by miRNA microarray in order to identify those with the most pronounced differential expression. The results were verified by quantitative RT-PCR (RT-qPCR) for miR-186, miR-3651 and miR-494 using 57 samples of patients and 33 samples of healthy volunteers. Receiver operating characteristic (ROC) curves and the highest Youden index were calculated in order to assess cut-off points (COPs) that allowed the distinguishing of blood samples of OSCC patients from those of healthy volunteers. Significantly different expression rates were found for miR-186 (p=0.01), miR-3651 (p=0.0001) and miR-494 (p=0.004) between the OSCC patients and healthy controls. In the OSCC patients, there was a 2-fold upregulation for miR-494 and miR-3651 and a 2-fold downregulation for miR-186. Based on the determined COPs, significant correlations between miR-3651 overexpression and lymph node status (p=0.04), tumor grade (p=0.02) and clinical stage (p=0.04) were indicated. Aberrant expression levels of miR-186, miR-494 and miR-3651 in whole blood samples of OSCC patients may provide the possibility to establish a minimally invasive screening method for OSCC.
EVALuna2:6555